(untitled) (Journal of Economic Research & Business Administration, 2018)
The article discusses the changing role of the modern university in connection with the development of an innovative economy and the transfer of knowledge on an international scale. The transition to modern production, based on advanced technologies and characterized by high technology-intensiveness, makes new demands on the field of higher education. The role of higher education institutions as a source of innovative developments in the country, as well as training centers for the innovation economy, is growing. The University acts as one of the main elements of the innovation system of the region, participating in the generation, accumulation and dissemination of knowledge. Along with business and government, the university determines the structure of the regional innovation system, influencing the socio-economic development of the region. The authors considered the main participants of the regional innovation system, their role in the formation of the regional ecosystem. The article shows that the interaction of the university and the regional innovation system can lead to the emergence of positive effects for all participants of RIS, which arise as a result of the formation of a single industrial ecosystem. The main positive effects from the ecosystem development for the economy of the region, higher educational institutions, as well as graduates are highlighted. The authors have revealed the formation of the innovation infrastructure in the universities of the Republic of Kazakhstan, which is the foundation for the inclusion of the university in the innovation processes of the region. The features of various elements of the innovation infrastructure, which allow the university to integrate into regional innovation processes, are revealed. The composition of the innovation infrastructure of leading universities, which occupy the first four places in the ranking of universities QS-2019 in the Republic of Kazakhstan, is considered. The main tasks of the functioning of commercialization offices in universities of the republic are determined.